Reflexões acerca da categoria trabalho na ontologia social de György Lukács - Duarte, Cláudio Aparecido (2011)
The object of this study falls in a reflection about György Lukács ' work category in your ontology. Therefore, how would the modal category work be situated according to materialist conception of History? This is the situation that will be addressed on this study. According to the lukacsian believe the modal category work would have in this conception the genesis of social being as well other categories. Thus, also is the basis of primary teleologies derived from the close relationship between man and nature as he could produce concrete conditions of his existence as the secondary theologies, which means, his conscience or what his conscience would produce. When studying the complex modal work, still according to Lukács, there are three important categories, in other words, alienation (Entäussaerung) And strangeness (Entfremdung) Alienation (Entäussaerung). While exteriorization/objectification, although the objectification is different of exteriorization both conceptions would be inseparable. In regards to strangeness (Entfremdung) in its s social-historic process it would involve how to be human in a specific moment of the development of productive forces. Consequently, work would be the structural axis of Marxist work what is evident when Lukács has contact with philosophical-economical manuscripts and this contact would transform his studies drastically. Thus, Karl Marx 's thoughts would be based mainly in a necessarily ontological dimension, from the thing itself, the ontological essence of the matter treated